THE EFFECT OF DIABETES SELF MANAGEMENT EDUCATION (DSME) ON SELF EFFICACY IN TYPE II DIABETES MELLITUS PATIENTS - Subkhan, Mohammad; Firman, Firman; Agustiningsih, Ida (Institute for Research and Community Service of Health Polytechnic of Kerta Cendekia, Sidoarjo, 2024)
Background: Diabetes mellitus (DM) is a health problem in the world. Currently, the number of DM cases globally has reached 537 million people, and Indonesia ranks fifth highest in the world. Low knowledge and dietary compliance are a problem that continues to contribute to new cases and relapses of old cases characterized by uncontrolled increases in blood sugar. This is caused by low self-efficacy which is characterized by feelings of hopelessness. Objectives: The aim of this research was to determine the effect of Diabetes Self-Management Education (DSME) on self-efficacy in type II Diabetes Mellitus patients. Methods: This study used a Quasy-experimental design, with a pretest posttest equivalent control group design, the sample size was 68 type II DM patients, consisting of 34 intervention groups and 34 control groups. Self-efficacy data was collected using the DMSES (Diabetes Management Self Efficacy Scale) questionnaire. Univariate analysis was used to describe the frequency distribution of respondents, mean, median and standard deviation. Next, bivariate analysis used the Wilcoxon test. Results: There was a significant difference in the difference in mean value self-efficacy between before and after intervention with p-value 0.000 < 0.05. Conclusion: Diabetes Management Self Efficacy Scale is effective increase self-efficacy. Thus, DSME can be an alternative intervention to overcome problems and prevent complications in DM patients.